2021
DOI: 10.13189/ujer.2021.090205
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Online Video Games in Enhancing EFL Learners' Communication Skills

Abstract: The Information Age has paved immense pathways for the emergence of technology, which led to eventually a complete digitalization of our communities. An ideal example of this advent is the continued growth of online video games (OVG) worldwide between youngsters and adults. To this end, our primary purpose was to understand and learn more about the diverse effects of online video games on EFL learners at the extent to which OVGs can be applied, as a new technique in academic settings. To go deeply through this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…It has been found that generally, video games are perceived as computerized games which require player input to manipulate certain elements within (Wilen-Daugenti, 2009). Video games facilitate active EFL acquisition and learning by presenting authentic situations in which language is used in accordance with various contexts, allowing for linguistic skill enhancements (Toufik & Hanane, 2021). Furthermore, video games provide features such as visuals, texts, sounds, and usage of lexical items.…”
Section: Video Games' Roles In Learning Englishmentioning
confidence: 99%
“…It has been found that generally, video games are perceived as computerized games which require player input to manipulate certain elements within (Wilen-Daugenti, 2009). Video games facilitate active EFL acquisition and learning by presenting authentic situations in which language is used in accordance with various contexts, allowing for linguistic skill enhancements (Toufik & Hanane, 2021). Furthermore, video games provide features such as visuals, texts, sounds, and usage of lexical items.…”
Section: Video Games' Roles In Learning Englishmentioning
confidence: 99%
“…98% выборки считают онлайнвидеоигры полезными для изучения английского языка, 72% отметили положительное влияние на навы-ки говорения и аудирования. Отмечалось благоприятное влияние на навыки межкультурной коммуникации, так как среди игроков есть представители разных национальностей [23].…”
Section: данные исследованийunclassified
“…Based on the results demonstrated by Toufik and Hanane (2021), League of Legends is responsible for enhancing players' intercultural competence by developing their awareness of intercultural differences and knowledge about the values, beliefs, and practices of other cultures. However, there have been some limitations and ambiguities during the Covid-19 pandemic.…”
Section: League Of Legends In Developing Learners' Iccmentioning
confidence: 99%